2005
DOI: 10.1590/s1516-35982005000500016
|View full text |Cite
|
Sign up to set email alerts
|

Estudo de definição alternativa da probabilidade de permanência no rebanho para a raça Nelore

Abstract: Uma definição alternativa de permanência no rebanho foi estudada em comparação à definição usual. Na definição usual, foram consideradas vacas com pelo menos três partos até os 76 meses de idade como valor 1 e vacas com menos de 3 partos com valor zero. A definição alternativa considerou os valores 0, 1, 2 e 3, respectivamente, para vacas com menos de três, com três, quatro ou cinco partos até os 76 meses de idade. Foram obtidas estimativas de herdabilidade e preditas as DEPs (Diferenças Esperadas na Progênie)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Therefore, direct selection for STAY would not imply genetic gain in the population studied. Marcondes et al (2005) and Nieto et al (2007) obtained similar heritability estimates for Nelore and Canchim animals evaluated at 76 months of age using a sire model. A slightly higher heritability estimate (0.12) was reported by Silva et al (2003) for Nelore cows, considering STAY at six years of age and using an animal model.…”
Section: Heritabilitymentioning
confidence: 63%
See 1 more Smart Citation
“…Therefore, direct selection for STAY would not imply genetic gain in the population studied. Marcondes et al (2005) and Nieto et al (2007) obtained similar heritability estimates for Nelore and Canchim animals evaluated at 76 months of age using a sire model. A slightly higher heritability estimate (0.12) was reported by Silva et al (2003) for Nelore cows, considering STAY at six years of age and using an animal model.…”
Section: Heritabilitymentioning
confidence: 63%
“…Several studies on beef cattle have reported genetic parameter estimates for stayability using Bayesian inference in Nelore Marcondes et al, 2005;Van Melis et al, 2007), Canchim (Nieto et al, 2007) and Caracu (Queiroz et al, 2007). However, there are few studies that investigate relationships between stayability and body weight, scrotal circumference and age at first calving (Silva et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this trait shows low heritability and is therefore not commonly used as a selection criterion in beef cattle. Heritability values reported by [ 9 ] and [ 10 ] for STAY in Nellore cattle were 0.07 and 0.10, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Usually the trait is analyzed by defining two categories, known as heifer pregnancy (Eler et al, 2004;Boligon, Albuquerque, 2011). However, a study with Nellore cattle argued that the use of polychotomous categories has a higher ability to detect genetic variation than the traditional binary approach (Marcondes et al, 2005).…”
Section: Introductionmentioning
confidence: 99%